2015
DOI: 10.1111/jch.12525
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ambulatory Blood Pressure Monitoring on Reclassification of Hypertension Prevalence and Control in Older People in Spain

Abstract: Ambulatory blood pressure monitoring (ABPM) accurately classifies blood pressure (BP) status but its impact on the prevalence and control of hypertension is little known. The authors conducted a cross-sectional study in 2012 among 1047 individuals 60 years and older from the follow-up of a population cohort in Spain. Three casual BP measurements and 24-hour ABPM were performed under standardized conditions. Approximately 68.8% patients were hypertensive based on casual BP (≥140/90 mm Hg or current BP medicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 52 publications
1
24
1
6
Order By: Relevance
“…Ninety-five participants died during follow-up; from the remaining 2519 subjects, 2037 provided updated information for the phone interview, the physical examination, diet and medication. Baseline sociodemographic and clinical characteristics of the participants at the inception of the cohort were reasonably similar to those who did not participate [28].…”
Section: Study Design and Participantsmentioning
confidence: 80%
See 2 more Smart Citations
“…Ninety-five participants died during follow-up; from the remaining 2519 subjects, 2037 provided updated information for the phone interview, the physical examination, diet and medication. Baseline sociodemographic and clinical characteristics of the participants at the inception of the cohort were reasonably similar to those who did not participate [28].…”
Section: Study Design and Participantsmentioning
confidence: 80%
“…Data were taken from the Seniors-ENRICA cohort, whose methods have been previously reported [27,28]. In brief, this cohort was established between 2008 and 2010 with 2614 non-institutionalized individuals selected through stratified random sampling from the population aged 60 years and older in Spain.…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The daunting reality is that only half of all Spanish individuals were within the normal range for both casual BP and ABPM and less than half of individuals with elevated casual BP and ABPM were receiving antihypertensive medication. 12 The concluding messages from the Spanish study are that, compared with casual BP measurement, ABPM led to a reduction in the proportion of older individuals recommended for hypertension treatment and a substantial increase in the proportion of those whose hypertension was controlled. ABPM would reduce misdiagnosis, ensure that the right people are treated with BP-lowering drugs, and reduce the number of patients treated for hypertension.…”
Section: Use Of Abpm To Assess Treatment Current Evidence and Recommementioning
confidence: 96%
“…One analysis of the Spanish database again supports the use of ABPM as a means of gaining greater insight into the subtleties of drug effects on BP. 12 The study found that 700,000 elderly individuals would have been spared medication if ABPM, instead of casual BP, had been performed. On the other hand, the percentage of patients considered eligible for treatment increased by 6% with ABPM, which amounted to 350,000 elderly patients.…”
Section: Use Of Abpm To Assess Treatment Current Evidence and Recommementioning
confidence: 98%